Pattern of Major Congenital Anomalies of the Gastrointestinal Tracts among Live Neonates at Al-Mukalla,Yemen - A Jawass , Mazin; ABahwal , Saleh; S Bakhalah, Ahmed; F Basalilah , Ashraf (Diyala Journal of Medicine, 2022)
Background: Major Congenital anomalies of the gastrointestinal tract(GIT) is a life threating condidition usually diagnosed in the neonatal period. Objective: To evaluate the prevalence of major congenital anomalies among live births at Al-Mukalla,Yemen. Patients and Methods: A hospital-based, descriptive cross sectional study was conducted during 2 years period, from January 1st 2019 to December 31th 2020 and include live neonates aged ≤ 4 weeks who were admitted with major congenital gastrointestinal anomalies. Results: The study include 62 neonates with major congenital GIT anomalies.The most common was imperforate anus in 41.9% followed by esophageal atresia with or without TEF in 24.2%, then hirschprung’s disease in 19.4%. Males are more common (61.3%) than females (38.7%).The incidence is 7.7 per 10.000 newborn. Isolated major GIT anomalies occurs in 64.5%, while associated extra -GIT anomalies occurs in 35.5% , the most common was congenital heart diseases that occurs in 17.7% of cases .The majority neonates were term in 90.3%, with birth weight ≥ 2.5 kg in 88.7%. Most mothers were < 35 years in 67.7% ,with positive parental consanguinity occurs in 37% of cases. Conclusion: High incidence of major Malformation were observed.